2018
DOI: 10.3892/or.2018.6726
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key tumorigenesis‑related genes and their microRNAs in colon cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors and its development involves multi-gene driven processes that affect the digestive system. The objective of this study was to identify tumorigenesis-associated gene signatures using microarray expression profiling data. The gene expression profiling of GSE39582, a dataset containing 566 colon cancer samples and 19 non-tumoral colorectal mucosae was downloaded from Gene Expression Omnibus (GEO) database. A total of 439 differentially expressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Due to high rate of colorectal cancer-related deaths worldwide [14, 15], the miRNA profile in biopsies and serum has been extensively studied for this condition [1620] but the lack of more comprehensive studies in both tissue and serum from the same patients and the repeatability for the identified miRNAs in different conditions is needed. Therefore, the goal of our study was to investigate the populations of miRNAs expressed in colorectal cancerous tissue when compared with a healthy adjacent tissue and serum from the same patients, to determine potential new biomarkers for early detection, prediction of patient recovery and future more personalized therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high rate of colorectal cancer-related deaths worldwide [14, 15], the miRNA profile in biopsies and serum has been extensively studied for this condition [1620] but the lack of more comprehensive studies in both tissue and serum from the same patients and the repeatability for the identified miRNAs in different conditions is needed. Therefore, the goal of our study was to investigate the populations of miRNAs expressed in colorectal cancerous tissue when compared with a healthy adjacent tissue and serum from the same patients, to determine potential new biomarkers for early detection, prediction of patient recovery and future more personalized therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the expression of other TRP channels appears to be decreased in cancer. For instance, TRPC4 channels in renal carcinoma (Veliceasa et al, 2007), TRPM6 in colorectal tumors (Xie et al, 2018), TRPV4 in skin and bladder tumor cells (Fusi et al, 2014;Mizuno et al, 2014;Yu et al, 2019) or the TRPV6 in lung carcinomas (Fan et al, 2014). In conclusion, the TRP channels superfamily expression levels have been described to be either up or down regulated in different tumors ( Table 1).…”
Section: Trp Calcium Permeable Channelsmentioning
confidence: 93%
“…Gene downregulation (Xie et al, 2018;Anderson et al, 2019) TRPM7 Breast, pancreas, ovarian, gastric and colorectal…”
Section: ) Trpm6 Colorectalmentioning
confidence: 99%
“…On these bases, TRPM6 and TRPM7 could be potential players in CRC. Indeed, it was reported that TRPM6 is downregulated in CRC tissues on mRNA level [120,123], and its higher expression is correlated with an increased overall survival [123]. On the other hand, TRPM7 was suggested to be upregulated in CRC on mRNA level [151].…”
Section: Colorectal Cancermentioning
confidence: 99%